Previous and Prospective Career Mobility, Client Capture, and Compromised Professional Judgment: The Withholding of Known Relevant Prior Art by Patent Lawyers on Behalf of Their Clients - Chari, Mukund; Steensma, H. Kevin; Connaughton, Charles (Organization Science, 2020)
Client capture is the process by which professionals become so dependent on certain clients that their professional judgment is compromised. We explore whether there are systematic differences across professionals in their likelihood of improperly biasing their judgment in the interests of clients on whom they highly depend. To do so, we examine the disclosure of prior art by patent lawyers when representing client patent applications submitted to the U.S. Patent and Trademark Office (USPTO). Lawyers are obligated professionally to disclose all relevant prior art of which they are aware even if, in doing so, their clients receive narrower intellectual property rights. We suggest that patent lawyers are generally more dependent on clients with whom they repeatedly engage and when they have numerous similar clients. We find, however, that the influence of such dependency on lawyers’ withholding prior art is greater when they have entered the legal profession through a regulatory employment revolving door. Specifically, regulatory experience as a USPTO patent examiner provides patent lawyers with unique insight that enables them to compromise their judgment on behalf of clients on whom they depend. Further, patent lawyers who are associates in their law firms are more inclined than are partners to withhold prior art on behalf of clients with whom they repeatedly engage. Because associates’ employment with their professional service firms is relatively insecure, compromising their professional judgment on behalf of clients with whom they repeatedly engage is more alluring in their efforts to enhance future employment prospects.